Penurunan Stunting Berbasis Stakeholder di Kabupaten Agam - Asiah, Nur; Khairul, Khairul (Indo-MathEdu Intellectuals Journal, 2025)
The policy for accelerating the reduction of stunting is a government policy aimed at preventing and reducing cases of stunting. The implementation of the policy for the rapid reduction of stunting in Agam Regency involves various parties. In optimizing the roles of each stakeholder involved, it is necessary to identify the roles of stakeholders. The aim of this research is to identify stakeholders and their roles. This research uses a qualitative descriptive research method. The source of data is interviews with informants. The data analysis technique used is qualitative data analysis with stages of data reduction, data presentation, and drawing conclusions. The research results show that stakeholders in the implementation of the stunting reduction acceleration policy in Agam Regency, based on their roles in the policy implementation in Agam Regency, have roles as policy creators, coordinators, implementers, facilitators, and accelerators. The roles performed by stakeholders meet the classification of stakeholder roles, although there are still some obstacles and challenges. The factors hindering the roles of stakeholders come from the perspectives of actors and the participation of actors.